GaAs(001): Surface Structure and Optical Properties - Schmidt, Wolf Gero; Bechstedt, F.; Fleischer, K.; Cobet, C.; Esser, N.; Richter, W.; Bernholc, J.; Onida, G. (physica status solidi (a))

Towards a Complete Many-Body Description: Optical Response of Real Surfaces - Bechstedt, F.; Schmidt, Wolf Gero; Hahn, P.H. (physica status solidi (a))

Theory for Modeling the Optical Properties of Surfaces - Onida, G.; Schmidt, Wolf Gero; Pulci, O.; Palummo, M.; Marini, A.; Hogan, C.; Del Sole, R. (physica status solidi (a))

X-ray diffraction analysis of the gallium-rich surface of GaAs(001) - Paget, D.; Garreau, Y.; Sauvage, M.; Chiaradia, P.; Pinchaux, R.; Schmidt, Wolf Gero (Physical Review B)

First-principles study of InP and GaP(001) surfaces - Pulci, O.; Lüdge, K.; Vogt, P.; Esser, N.; Schmidt, Wolf Gero; Richter, W.; Bechstedt, F. (Computational Materials Science)

On the origin of resonance features in reflectance difference data of silicon - Hingerl, K; Balderas-Navarro, R.E; Bonanni, A; Tichopadek, P; Schmidt, Wolf (Applied Surface Science)

Terrace and step contributions to the optical anisotropy of Si(001) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Physical Review B)

Optical Anisotropy of theSiC(001)-(3×2)Surface: Evidence for the Two-Adlayer Asymmetric-Dimer Model - Lu, Wenchang; Schmidt, Wolf Gero; Briggs, E. L.; Bernholc, J. (Physical Review Letters)

Improved ultrasonic density sensor with reduced diffraction influence - Püttmer, A.; Lucklum, R.; Henning, Bernd; Hauptmann, P. (Sensors and Actuators A: Physical)

Novel Concepts for Teaching Particle Technology - Schmid, Hans-Joachim; Peukert, Wolfgang (chemical engineering education)

Aus dem Französischen ins Italienische: K. Mulligan, Métaphysique et ontologie. In: Aut-Aut, 310-311, 116-143

Die Entdeckung der Leibnizschen Logik - Peckhaus, Volker (Medium Mathematik. Anregungen zu einem interdisziplinären Gedankenaustausch, Bd. 1)

Oskar Beckers Stellung in der Geschichte der Modallogik - Peckhaus, Volker (Die Philosophie und die Wissenschaften. Zum Werk Oskar Beckers)

Regressive Analysis - Peckhaus, Volker (Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy)

Hilbert’s Paradox - Peckhaus, Volker; Kahle, Reinhard (Historia Mathematica)
Rezension: Zbl. Math. 0996.01012 (I. Grattan-Guinness); The College Mathematics Journal 34 (2003), 167 (P. Ross).

Analytically Closed Calculation of the Conduction and Switching Losses of Three-Phase AC-AC Sparse Matrix Converters - Schafmeister, Frank; Baumann, Martina; Kolar, Johann (Proc. 10th International Power Electronics and Motion Control Conference (EPE-PEMC))

Novel Three-Phase AC-DC-AC Sparse Matrix Converter - Kolar, Johann; Baumann, Martina; Schafmeister, Frank; Ertl, Hans (Proc. 17th IEEE Applied Power Electronics Conf. (APEC))

Analyse der Regelung einer permanenterregten Synchronmaschine bei Speisung durch einen dreiphasigen Sparse-Matrix-Konverter - Schafmeister, Frank; Kolar, Johann (Proc. Ansoft Inspiring Design Workshop)

High dynamic control of a three-level voltage-source-converter drive for a main strip mill - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Comparison of low voltage topologies for voltage regulator modules - Wetzel, H.; Fröhleke, N.; Meier, F.; Ide, P. (Conference Record of the 2002 IEEE Industry Applications Conference. 37th IAS Annual Meeting (Cat. No.02CH37344))

Optimisation of Inductors in Power Converters Feeding High Power Piezoelectric Motors - Njiende, H. D.; Fröhleke, N. (Journal of Electrical & Electronics Engineering, Australia)

Sensorless Speed Control of Permanent Magnet Synchronous Machines for Low Speed and Standstill - Kiel, J.; Bünte, A.; Beinecke, S. (Power Conversion and Intelligence Motion (PCIM 2002), Nuremberg, Germany)

Resonant Power Converter for Ultrasonic Piezoelectric Converter, Bremen Germany - Kauczor, C.; Schulte, T.; Fröhleke, N. (ACTUATOR 2002, 8th International Conference on New Actuators,)

Application, Calculation and Analysis of the Doubly Fed Longstator Linear Motor for the Wheel-on-Rail NBP Test Track - Yang, B.; Grotstollen, H. (EPE-PEMC 2002, Dubrovnik & Cavta)

PWM-Converter for Travelling Wave Type Ultrasonic Motors - Schulte, T.; Fröhleke, N. (ACTUATOR 2002, 8th International Conference on New Actuators, Bremen Germany)

Konzept zur berührungslosen Energieübertragung mit doppeltgespeistem Langstatorlinearmotor - Pottharst, A.; Grotstollen, H. (SPS/IPC/Drives 2002, Nürnberg)

Regelung doppeltgespeister Antriebe ohne mechanischen Lagesensor am Beispiel eines Linearmotors - Henke, M.; Grotstollen, H. (SPS/IPC/Drives 2002, Nürnberg)

Macfarlane, Alexander (1851–1913) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Harley, Robert (1828–1910) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Neil, Samuel (1825–1901) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 2: I–Z)

Ellis, Robert Leslie (1817–59) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 1: A–H)

Bentham, George (1800–84) - Peckhaus, Volker (The Dictionary of Nineteenth-Century British Philosophers, Bd. 1: A–H)

Georg Misch, Logik und Einführung in die Grundlagen des Wissens. Die Macht der antiken Tradition in der Logik und die gegenwärtige Lage. hg. v. Gudrun Kühne-Bertram, Critique & Humanism Publishing House: Sofia 1999 (Studia Culturologica, Sonderheft 1999) - Peckhaus, Volker (Zeitschrift für allgemeine Wissenschaftstheorie)

José Ferreirós, Labyrinth of Thought. A History of Set Theory and Its Role in Modern Mathematics. Birkhäuser Verlag, Basel/Boston/Berlin, 1999 (Science Networks. Historical Studies, Volume 23) - Peckhaus, Volker (Studia Logica)

Norbert Hinske, Stellenindex zu „Immanuel Kant’s Logik“ (Jäsche-Logik). Studienausgabe zu Kant-Index Band 2, frommann-holzboog, Stuttgart-Bad Cannstatt, 1999 - Peckhaus, Volker (Studia Logica)

Frank-Peter Hansen, "Geschichte der Logik des 19. Jahrhunderts. Eine kritische Einführung in die Anfänge der Erkenntnis- und Wissenschaftstheorie", Königshausen & Neumann: Würzburg 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Born, Rainer, “Frege”, In: Stuart G. Shanker (Hg.), Routledge History of Philosophy, Bd. IX: Philosophy of Science, Logic and Mathematics in the Twentieth Century, Routledge: London 1996, 124–156 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rusnock, Paul, “Philosophy of Mathematics: Bolzano’s Response to Kant and Lagrange”, In: Rev. Hist. Sci. 52 (1999), No.3–4, 399–427 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kreiser, Lothar. "Gottlob Frege. Leben – Werk – Zeit", Felix Meiner Verlag: Hamburg 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Pechenkin, A. A., “Operationalism as the Philosophy of Soviet Physics: The Philosophical Background of L.I. Mandelstam and his School”, In: Synthese 124 (2000), 407–432 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rodríguez-Consuegra, Francisco, “Nominal Definitions and Logical Consequence in the Peano School”, In: Theoria. Segunda Epoca 12, no. 28 (1997), 125–137 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Waldegg, Guillermina, “Ontological Convictions and Epistemological Obstacles in Bolzano’s Geometry”, In: Science and Education 10 (2001), 409–418 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tait, W. W., “Gödel’s Unpublished Papers on Foundations of Mathematics”, In: Philosophia Mathematica (3) 9 (2001), 87–126 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stüven, Norbert, „Mathematisches Problemlösen: geschlechtsabhängig?“, In: Mitt. Math. Ges. Hamb. 16 (1997), 87–98 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sandu, Gabriel/Hyttinen, Tapani, “IF Logic and the Foundations of Mathematics”, In: Synthese 126 (2001), 37–47 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Friedman, Michael. "Reconsidering Logical Positivism", Cambridge University Press: Cambridge 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dummett, Michael. "Frege and other Philosophers", Paperback, Clarendon Press: Oxford 1996 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Linsky, Bernard. "Russell’s Metaphysical Logic", CSLI Publications: Stanford, CA 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Moore, Gregory H., “The Prehistory of Infinitary Logic: 1885–1955”, in: Maria Luisa Dalla Chiara u.a. (Hgg.), Structures and Norms in Science. Volume two of the 10th International Congress of Logic, Methodology and Philosophy of Science, Florence, Italy, August 1995, Dordrecht: Kluwer Academic Publishers 1997, 105–123 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Reichel, Hans-Christian, “How Can or Should the Recent Development in Mathematics Influence the Philosophy of Mathematics?”, in: Werner De Pauli-Schimanovich u.a. (Hgg.), The Foundational Debate. Constructivity and Complexity in Mathematics and Physics, Kluwer: Dordrecht 1995, 259–268 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Friedman, Michael, “Geometry, Construction, and Intuition in Kant and his Successors”, in: Gila Sher u.a. (Hgg.), Between Logic and Intuition. Essays in Honor of Charles Parsons, Cambridge University Press: Cambridge 2000, 186–218 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Peña, Lorenzo, “The Coexistence of Contradictory Properties in the Same Subject According to Aristotle”, In: Apeiron 32 (1999), no. 3, 203–209 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Reprint von MR 2002h:01003])

Degnan, Michael J., “What is the Scope of Aristotle’s Defense of the PNC”, In: Apeiron 32 (1999), no. 3, 243–274 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [ Reprint von MR 2002h:01005])

Koriako, Darius. "Kants Philosophie der Mathematik. Grundlagen, Voraussetzungen, Probleme", Felix Meiner Verlag: Hamburg 1999 (Kant-Forschungen; 11) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wessel, Horst. "Logik und Philosophie", Logos Verlag: Berlin 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Empfehlen oder Vorschreiben? Zur Formulierung und Legitimierung der Stilnormen in den praktischen Stilistiken nach 1945 - Ptashnyk, Stefaniya (Studia Linguistica XXI)

Wedin, M.V., “The Scope of Non-contradiction: a Note on Aristotle’s ‘Elenctic’ Proof in Metaphysics Γ 4”, In: Apeiron 32 (1999), no. 3, 231–242 - Peckhaus, Volker (Mathematical Reviews)

Peña, Lorenzo, “The Coexistence of Contradictory Properties in the Same Subject According to Aristotle”, In: Apeiron 32 (1999), no. 3, 203–209 - Peckhaus, Volker (Mathematical Reviews)

Degnan, Michael J., “What is the Scope of Aristotle’s Defense of the PNC”, In: Apeiron 32 (1999), no. 3, 243–274 - Peckhaus, Volker (Mathematical Reviews)

Thom, Paul, “The Principle of Non-contradiction in Early Greek Philosophy”, In: Apeiron 32 (1999), no. 3, 153–170 - Peckhaus, Volker (Mathematical Reviews)

Baltzly, Dirk, “Aristotle and Platonic Dialectic in Metaphysics Γ 4”, In: Apeiron 32 (1999), no. 3, 171–202 - Peckhaus, Volker (Mathematical Reviews)

Schmitz, Markus, „Erkenntnistheorie der Zahldefinition und philosophische Grundlegung der Arithmetik unter Bezugnahme auf einen Vergleich von Gottlob Freges Logizismus und platonischer Philosophie (Syrian, Theon von Smyrna u.a.)“, In: Journal for General Philosophy of Science 31 (2001), 271–305 - Peckhaus, Volker (Mathematical Reviews)

Dejnožka, Jan, “Origins of Russell’s Early Theory of Logical Truth as Purely General Truth: Bolzano, Peirce, Frege, Venn, or MacColl?”, In: Modern Logic 8 (2000/2001), nos. 3–4, 21–30 - Peckhaus, Volker (Mathematical Reviews)

Bennett, Jonathan, “Infallibility and Modal Knowledge in Some Early Modern Philosophers”, In: Mathematics and Necessity, London, 1998, Proc. Br. Acad. 103 (2000), 139–166 - Peckhaus, Volker (Mathematical Reviews)

Moore, Gregory H., “Hilbert on the Infinite: The Role of Set Theory in the Evolution of Hilbert’s Thought”, In: Historia Mathematica 29 (2002), 40–64 - Peckhaus, Volker (Mathematical Reviews [)

Den Nagel auf den Kopf treffen – Wortverbindungen mehr oder weniger fest. Bericht von der 39. Tagung des Instituts für Deutsche Sprache - Ptashnyk, Stefaniya (Deutsche Sprache: Zetischrift für Theorie, Praxis, Dokumentation. Heft 4/2002. Nachgedruckt in: (a) Sprachreport, Heft 2/2003. Hrsg. vom Institut für Deutsche Sprache. Mannheim. S. 5-12. (b) Jahresbericht des Instituts für Deutsche Sprache 2003. Mannheim, S. 30-38.)

Quasiparticle calculations for point defects on semiconductor surfaces - Hedström, Magnus; Schindlmayr, Arno; Scheffler, Matthias (Physica Status Solidi B)
We discuss the implementation of quasiparticle calculations for point defects on semiconductor surfaces and, as a specific example, present an ab initio study of the electronic structure of the As vacancy in the +1 charge state on the GaAs(110) surface. The structural properties are calculated with the plane‐wave pseudopotential method, and the quasiparticle energies are obtained from Hedin's GW approximation. Our calculations show that the 1a″ vacancy state in the band gap is shifted from 0.06 to 0.65 eV above the valence‐band maximum after the self‐energy correction to the Kohn‐Sham eigenvalues. The GW result is in close agreement with a recent surface photovoltage imaging measurement.

Utility and Universality versus Utility and the General Good - Hagengruber, Ruth Edith (Philosophie und Wissenschaft. Tagungsakten zum 70. Geburtstag von Wolfgang H. Müller)

Philosophie und Wissenschaft. Tagungsakten zum 70. Geburtstag von Wolfgang H. Müller

An OCL Extension for Real-Time Constraints - Flake, Stephan; Müller, Wolfgang (Advances in Object Modelling with the OCL)
The Object Constraint Language (OCL) was introduced to support the specification of constraints for UML diagrams and is mainly used to formulate invariants and operation pre- and postconditions. Though OCL is also applied in behavioral diagrams, e.g., as guards for state transitions, it is currently not possible to specify constraints concerning the dynamic behavior and timing properties of such diagrams. This article discusses OCL’s application for the dynamic behavior of UML Statechart diagrams and presents an OCL extension for specification of state-oriented time-bounded constraints.We introduce operations to extract state configurations from diagrams and define additional predicates over states and state configurations. The semantics of our OCL extension is given by employing time-bounded Computational Tree Logic (CTL) formulae. An example of a flexible manufacturing system with automated guided vehicles demonstrates the application of our extension.
Keywords: Model Check Temporal Logic Object Constraint Language Execution Path Kripke Structure

Werkzeugintegration und -verwaltung in heterogenen Computernetzwerken - Eikerling, H. J.; Müller, Wolfgang; Wegener, J. (it+ti)

Den Wortschatz entdecken: Theorie und Praxis der Förderung semantisch-lexikalischer Sprachkompetenzen im Unterricht und Therapie. Gleichzeitig Hausarbeit zum 2. Staatsexamen für das Lehramt für Sonderpädagogik - Albers, Timm

Pedro braucht Zutaten: Sprachförderung in einer Kleingruppe - Albers, Timm (Zeitschrift für Heilpädagogik)

Quand des apprenants du français parlent entre eux de leur langue cible – activités métadiscursives dans la communication interalloglotte - Behrent, Sigrid (Marges Linguistiques)

Vom Arcanum zur Hieroglyphe. Das Geheimnis der frühneuzeitlichen Staaten im Geschichtsdenken Leopold Rankes - Süßmann, Johannes (Das Geheimnis am Beginn der europäischen Moderne)

[Rez. v.] Michaela Völkel: Das Bild vom Schloss. Darstellung und Selbstdarstellung deutscher Höfe in Architekturstichserien 1600–1800. (Kunstwissenschaftliche Studien, Bd. 92.) München/Berlin, Deutscher Kunstverlag 2001 - Süßmann, Johannes (Historische Zeitschrift)

Was ist und wozu benötigten Adlige ästhetische Kompetenz? Versuch über die Architekturveduten Salomon Kleiners zu Schloß Pommersfelden - Süßmann, Johannes (Germanisch-Romanische Monatsschrift)
Keywords: Kleiner; Salomon; Vedute; Lothar Franz von Schönborn; Friedrich Carl von Schönborn; Kulturpatronage

[Art.] Erzählung - Süßmann, Johannes (Lexikon Geschichtswissenschaft. Hundert Grundbegriffe)

Gestaltung des Übergangs in die Sekundarstufe I: Maßnahmen an Grundschulen und weiterführenden Schulen in NRW. Ergebnisse einer Lehrerbefragung in Nordrhein-Westfalen - Leffelsend, S.; Bloh, Bea

'Opening up a can of worms’: Physicians’ Narrative Construction of Knowledge about Domestic Violence - Mildorf, Jarmila (Narrative Inquiry)

General Practitioners' Narrative Discourse on Domestic Violence: A Sociolinguistic Study - Mildorf, Jarmila

Time to Disclose, Timing Disclosure: GPs’ Discourses on Disclosing Domestic Abuse in Primary Care - McKie, Linda; Fennell, Barbara; Mildorf, Jarmila (Sociology of Health and Illness)

On the Modelling of the Electro-Hydrodynamic Flow Field in Electrostatic Precipitators - Schmid, Hans-Joachim (Flow, Turbulence and Combustion)
Electro-hydrodynamic (EHD) flows are investigated theoretically and numerically in this paper and results are presented for the flow field in model electrostatic precipitators (EPs). The resulting flow fields are shown in various representations and explained qualitatively. Numerical calculations with different flow models (non-turbulent and RANS) were conducted to investigate the influence of the flow model on the resulting secondary flows. Furthermore, a perturbation analysis is presented, leading to a simple differential equation of the Helmholtz type. This allows a more detailed view of the important mechanisms forming the secondary flows as well as being able to obtain a very fast estimation of the resulting flow field. The calculations reveal a strong influence of a vortex formation at the beginning of the precipitation zone on the whole flow field. Furthermore, a strong effect of the boundary conditions of the electric field and the operating parameters is shown.

Anistropic creep modeling based on elastic projection operators with applications to CMSX-4 superalloy - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)

Theoretical, numerical and identification aspects of a new model class for ductile damage - Mahnken, Rolf (International Journal of Plasticity)

Efficient Online and Offline Testing of Embedded DRAMs - Hellebrand, Sybille; Wunderlich, Hans-Joachim; A. Ivaniuk, Alexander; V. Klimets, Yuri; N. Yarmolik, Vyacheslav (IEEE Transactions on Computers)

Two-Dimensional Test Data Compression for Scan-Based Deterministic BIST - Hellebrand, Sybille; Liang, Hua-Guo; Wunderlich, Hans-Joachim (Journal of Electronic Testing - Theory and Applications (JETTA))

A Mixed-Mode BIST Scheme Based on Folding Compression - Liang, Huaguo; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal on Computer Science and Technology)

Originalität als inszenierte Epigonalität. Christoph Martin Wieland zwischen Klassik, Aufklärung und Romantik - van Laak, Lothar (Akten des X. Internationalen Germanistenkongresses Wien 2000 “Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert”)

Die Allegorie als hermeneutische Grenzsituation bei Johann Gottfried Herder - van Laak, Lothar (Grenzsituationen. Wahrnehmung, Bedeutung und Gestaltung in der neueren Literatur)

Rickettsien und Chlamydien: kleine Bakterien oder große Viren? - Kullmann, Harry (Unterricht Biologie)

Von Viren und Warzen - Papillomviren - Kullmann, Harry (Unterricht Biologie)

Gerhardus Alesius: Epigrammatum libellus, Wien 2000 (unter dem Titel: Plurima tamen Bilbilitano more elaborata) - Elit, Stefan (Journal of Neo-Latin Language and Literature NlatJb 4)

Lotichius und die römische Elegie, hg. v. Ulrike Auhagen u. Eckart Schäfer, Tübingen 2001 (NeoLatina 2) - Elit, Stefan (BMCR 06)

Ernst Haiger/Amelie Ihering/Carl Friedrich von Weizsäcker: Albrecht Haushofer, Ebenhausen 2002 - Elit, Stefan (sehepunkte 2, Nr. 12)

„Mouvance der Textsituation und des Textes (Heinrich von Morungen, MF 131, 25)“ - Egidi, Margreth (Akten des X. Internationalen Germanistenkongresses Wien 2000. „Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert“, unter Mitarbeit v. Hans Derkits, Bd. 5: Mediävistik und Kulturwissenschaften, betreut v. Horst Wenzel u. Alfred Ebenbauer; Mediävistik und Neue Philologie, betreut v. Ingrid Bennewitz, Werner Röcke u. Peter Strohschneider (Jahrbuch für Internationale Germanistik A, Kongressberichte 57))

„Poetik der Unterscheidung: Zu Frauenlobs Liedern“ - Egidi, Margreth (Studien zu Frauenlob und Heinrich von Mügeln. Festschrift für Karl Stackmann zum 80. Geburtstag)

„Der Immergleiche. Erzählen ohne Sujet: Differenz und Identität in ‚Flore und Blanscheflur‘“ - Egidi, Margreth (Literarische Leben. Rollenentwürfe in der Literatur des Hoch und Spätmittelalters. Festschrift für Volker Mertens zum 65. Geburtstag)

Michael Waltenberger, Das große Herz der Erzählung. Studien zu Narration und Interdiskursivität im ‚Prosa-Lancelot‘‘, Frankfurt/M. 1999 - Egidi, Margreth (Arbitrium 2002, H. 3)

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability